The adequacy of the Inspector-General Standing Orders (IGSO) in regulating the procedures of an identification parade for eyewitness identification in Malaysia / Siti Alina Mohd Adil Natkunasingham - Mohd Adil Natkunasingham, Siti Alina (2017)
This research attempts to provide insights on the adequacy of the Inspector-General Standing Orders (IGSO) in regulating the procedures of eyewitness identification parade in Malaysia. It is postulated that sole reliance on the IGSO guidelines has contributed to numerous unfair practices during the eyewitness identification parade in the Malaysian police departments. In assessing the adequacy of the IGSO in regulating eyewitness identification procedures, this paper reviews the laws on identification evidence in the United Kingdom for comparative analysis. Based on analysis of the law, semi-structured interviews and subsequent data analysis, the research concludes that the IGSO remains inadequate in governing the procedures of identification parade in the Malaysian police departments. Among prevalent issues are i) lack in manpower; and ii) time constraint among police officers, resulting in varying practices. Comparisons made with the United Kingdom’s Code D of PACE Act 1984 also found loopholes in Malaysia’s Part D226 guidelines in the IGSO, which necessitates an evaluation on the stated provisions. Further, the IGSO should be made publicly available, with the empowerment of the IGSO in police departments recommended. Stern actions should be taken on police officers who disregard the procedures. The procedures should also be considered to be inserted into the attachments of the Criminal Procedure Code (Act 593) which holds most of the directions in law enforcement. Upgrading police facilities is highly recommended, while police officers should be given intensive training on the subject. A designated Identification Officer for each police department is also advised to optimize manpower.